Unmasking the culprit: MAPCA masquerading as RV failure in post surgical correction of TOF. Issue 3 (March 2017) - Bhalgat, Parag; Naik, Abhijeet; Someshwar, Vimal; Joshi, Suresh
Abstract: Pulmonary regurgitation and right ventricular dilatation are major determinants of long-term follow up of surgically corrected tetralogy of Fallot. Occasionally, there are undiagnosed associated anomalies, which can exaggerate pulmonary regurgitation. The present report describes long-term effect of major aorto pulmonary collateral on right ventricular volume also a result of successful intervention. <Learning objective: Following pulmonary valvotomy in conotruncal anomalies there is development of significant pulmonary regurgitation. On long-term follow up, they are candidates for pulmonary valve replacement. A thorough search and management of associated defects (such as major aorto pulmonary collaterals, peripheral pulmonary stenosis) can reverse right ventricular dilatation and postpone pulmonary valve placement.>